2017
DOI: 10.1016/j.neuro.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Gestational exposure to perfluorooctanoic acid (PFOA): Alterations in motor related behaviors

Abstract: Perfluoroalkyl and polyfluoroalkyl substances are used in commercial applications and developmental exposure has been implicated in alterations in neurobehavioral functioning. While associations between developmental perfluorooctanoic acid (PFOA) exposure and human outcomes have been inconsistent, studies in experimental animals suggest alterations in motor related behaviors. To examine a dose-response pattern of neurobehavioral effects following gestational exposure to PFOA, pregnant CD-1 mice received PFOA (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 71 publications
(86 reference statements)
0
17
0
Order By: Relevance
“…2018; Hoffman et al 2010;Hoyer et al 2015;Rappazzo et al 2017) and negative (Lyall et al 2018;Rappazzo et al 2017;Stein and Savitz 2011;Stein et al 2013) associations between PFAS exposures and neurodevelopmental outcomes. Similarly, exposure to PFAS has been reported to cause behavioral toxicity in some (Goulding et al 2017;Johansson et al 2008;Long et al 2013;Sato et al 2009;Wang et al 2015), but not all (Butenhoff et al 2009), animal studies. In those studies where a positive relationship was revealed, affected behavioral end points included hyperactivity (Goulding et al 2017;Johansson et al 2009), reduced habituation (Johansson et al 2008), impairments in spatial learning and memory resulting from adult (Long et al 2013) and prenatal exposures (Wang et al 2015), and tonic convulsions in response to an ultrasonic stimulus (Sato et al 2009).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…2018; Hoffman et al 2010;Hoyer et al 2015;Rappazzo et al 2017) and negative (Lyall et al 2018;Rappazzo et al 2017;Stein and Savitz 2011;Stein et al 2013) associations between PFAS exposures and neurodevelopmental outcomes. Similarly, exposure to PFAS has been reported to cause behavioral toxicity in some (Goulding et al 2017;Johansson et al 2008;Long et al 2013;Sato et al 2009;Wang et al 2015), but not all (Butenhoff et al 2009), animal studies. In those studies where a positive relationship was revealed, affected behavioral end points included hyperactivity (Goulding et al 2017;Johansson et al 2009), reduced habituation (Johansson et al 2008), impairments in spatial learning and memory resulting from adult (Long et al 2013) and prenatal exposures (Wang et al 2015), and tonic convulsions in response to an ultrasonic stimulus (Sato et al 2009).…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, exposure to PFAS has been reported to cause behavioral toxicity in some (Goulding et al 2017;Johansson et al 2008;Long et al 2013;Sato et al 2009;Wang et al 2015), but not all (Butenhoff et al 2009), animal studies. In those studies where a positive relationship was revealed, affected behavioral end points included hyperactivity (Goulding et al 2017;Johansson et al 2009), reduced habituation (Johansson et al 2008), impairments in spatial learning and memory resulting from adult (Long et al 2013) and prenatal exposures (Wang et al 2015), and tonic convulsions in response to an ultrasonic stimulus (Sato et al 2009). Molecular results obtained in animal studies suggest that PFAS exposures may disrupt dopaminergic and/or calcium signaling pathways during neurogenesis (Hallgren and Viberg 2016;Johansson et al 2009;Lee and Viberg 2013;Liu et al 2010aLiu et al , 2010bZeng et al 2011).…”
Section: Discussionmentioning
confidence: 93%
“…Potential adverse effects of PFAS on the nervous system and functions have not been widely investigated. A few studies reported neurotoxicity of PFOS, PFHxS, and PFOA in cell culture systems (Slotkin et al 2008), as well as altered behavioral responses (Goulding et al 2017) and deficits in learning and memory ability in rodents (Viberg et al 2013). In contrast, no significant developmental neurotoxic effects were seen from prenatal exposure to PFOS in USEPA guideline–based studies with rats (Butenhoff et al 2009).…”
Section: Current Knowledge Of Pfas Toxicity In Experimental Modelsmentioning
confidence: 99%
“…Per uorinated compounds (PFCs) have been widely used in many areas, including industrial production, household supplies and even biomedical applications, because of their good chemical stability, and hydrophobic and oleophobic properties (A et al 2020; Kah et al 2020;Li et al 2019b;Sivaram et al 2020). It has been shown that PFCs can be found in the blood, liver, kidney, heart, and muscle, and the toxicity has been demonstrated in the liver (Filgo et al 2015;Wu et al 2017;Zhao et al 2016;Zheng et al 2017), as well as in neuro (Goulding et al 2017), cardiovascular (Lv et al 2018), and reproductive tissues (Lee et al 2017). And it has also been shown to be genotoxic (Butenhoff et al 2014), carcinogenic (Tsuda 2016), and immunotoxic (Di Nisio et al 2020; Liu and Gin 2018).…”
Section: Introductionmentioning
confidence: 99%